2014
DOI: 10.1371/journal.pone.0097334
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Changes in Plasma Levels of Sex Hormones in the Greater Rhea (Rhea americana), a South American Ratite with a Complex Mating System

Abstract: Seasonal rhythm in sex hormones has been extensively studied in birds, as well as its relationship with the type of mating system. The Greater Rhea (Rhea americana), a South American ratite species, reproduces seasonally and has a complex mating system: female-defense polygyny and sequential polyandry. The present study aimed at analyzing the endocrine basis of reproduction in this species and its relationship with its mating system. We used HPLC and electrochemiluminescence techniques to identify and measure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…This study is aggregating with previous reports that aims different aspect as hormones and sexual behavior (Leite & Codenotti 2005, Valdez et al 2014) that in Rio Grande do Sul, the reproductive period of the Greater Rhea occurs during spring and summer. Thereby the samples from 2005 and 2006 were made during the reproductive period.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…This study is aggregating with previous reports that aims different aspect as hormones and sexual behavior (Leite & Codenotti 2005, Valdez et al 2014) that in Rio Grande do Sul, the reproductive period of the Greater Rhea occurs during spring and summer. Thereby the samples from 2005 and 2006 were made during the reproductive period.…”
Section: Resultssupporting
confidence: 82%
“…In Rhea Americana were reported seasonality pattern in sex hormones (Valdez et al 2014) and macroscopic morphology of testicles and epididymis (Carvalho et al 2015). There is no report about spermatogenesis in this South American bird.…”
Section: Introductionmentioning
confidence: 84%
“…LEITE & CODENOTTI (2005) reported that in the Rio Grande do Sul, the reproductive period of Greater Rhea, happens in spring and summer. Sexual hormones in both sexes were reported in two different seasons (VALDEZ et al 2014). These reports are in agreement with the 2005 and 2006 collections.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, it is reasonable to assume that the higher FGM levels observed in this study during the breeding season are related to the high rate of male‐male fighting observed during this time of the year. High testosterone levels have also been recorded throughout the entire breeding period in Greater Rheas [Valdez et al, ], which would explain the increased agonist interactions between males during that period and the increased stress levels. Increased fecal glucocorticoid and androgen metabolite levels associated with greater rates of interaction and higher frequency of aggressive and courtship behaviors were observed by Corlatti et al [, ] in chamois territorial males, during the rut.…”
Section: Discussionmentioning
confidence: 99%